Spore special issue: Modernising farms: Paths to success - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2011)
The economic prospects of ACP countries depend on their ability to modernise the agricultural sector as a means to address poverty and foster growth. This special issue of Spore highlights the challenges, the crucial role of entrepreneurs and the importance of having all stakeholders work together to develop a common vision. As the issue demonstrates, agricultural transformation and modernisation are already underway in many of these countries, with valuable success stories to be shared from across the sector.